Cultivation Of Technical Hemp On Saline Soils With Drip Irrigation (Texas Journal of Agriculture and Biological Sciences, 2024)
This article describes that for the first time research was carried out on the culture of industrial hemp in the soil and climatic conditions of the Khavast district of the Syrdarya region, where 5 varieties were studied, which, with sufficient irrigation and compliance with agricultural cultivation technology, are quite possible to successfully cultivate. Breeding work was carried out by the method of individual selection of industrial hemp plants with the necessary improved characteristics for further research in order to create new local varieties for our Republic.